Food and beverage purchases at formal and informal outlets in Mexico - Irene Farah; Dalia Stern; Yenisei Ramírez; Nancy López-Olmedo; Carolina Pérez-Ferrer; Brent A Langellier; M Arantxa Colchero; Tonatiuh Barrientos-Gutierrez (Cambridge University Press, 2023)
Abstract Objective: To examine food and beverage purchasing patterns across formal and informal outlets among Mexican households' and explore differences by urbanicity and income. Design: Cross-sectional study of a nationally representative sample of households. We calculated the proportion of total food and beverage expenditure in each household by food outlet type overall and by urbanicity and income. We defined informal outlets as those which are not registered or regulated by tax and fiscal laws. Since some of the outlets within community food environments do not fall in clear categories, we defined a continuum from formal to informal outlets, adding mixed outlets as a category. Setting: Mexico. Participants: Mexican households (n 74 203) from the 2018 National Income and Expenditure Survey. Results: Of the total food and beverage purchases, outlets within the formal food sector (i.e. supermarkets and convenience stores) accounted for 15 % of the purchases, 13 % of purchases occurred in outlets within the informal food sector (i.e. street markets, street vendors and acquaintances) and 70 % in fiscally mixed outlets (i.e. small neighbourhood stores, specialty stores and public markets). Across levels of urbanicity and income, most food and beverage purchases occurred in mixed outlets. Also, purchases in informal and mixed outlets decreased as levels of urbanicity and income increased. In contrast to informal outlets, purchases in formal outlets were most likely from richer households and living in larger sized cities. Conclusions: Understanding where Mexican households shop for food is relevant to create tailored interventions according to food outlet type, accounting for regulatory and governance structures.